Evaluación del impacto socioeconómico del turismo rural comunitario en el desarrollo de la parroquia Saraguro, cantón Saraguro, provincia de Loja - León Puga, Paola Graciela (2023)
The present work entitled "Evaluation of the socioeconomic impact of rural community tourism in the development of the Saraguro parish, Saraguro canton, Loja province", had as its general objective Evaluate the socioeconomic impact of Community Rural Tourism in the development of the Saraguro parish, canton Saraguro, province of Loja. Likewise, three specific objectives were proposed such as: 1. Diagnose the reality of rural community tourism in the Saraguro parish, Saraguro canton, Loja province; 2. Evaluate the socioeconomic impacts of rural community tourism from the perception of its residents in the Saraguro parish, Saraguro canton, province of Loja and 3. Propose strategies to improve the development of rural community tourism in the Saraguro parish, Saraguro canton, province of shop. The methodology that was used as a basis was the analysis of the tourist profile, an interview directed towards the members who develop community rural tourism, phase 3 of the guide for the formulation of development plans in rural territories by Marvin Blanco; In addition to the methodology used from the research of Gabriela Catalina Guachisaca Masa on the perception of residents regarding the development of rural community tourism, finally this methodologies allowed the construction of a SWOT to later, through the strategic SWOT, determine the matrix of strategies. The results obtained from the survey applied on the tourist profile determined that the parish is visited by tourists of medium to high socioeconomic level; Likewise, through the interview it was possible to know that the residents are unaware of the development of rural community tourism since they argue that this activity generates benefits for a select group and that on the other hand public entities do not help development in the community. It is concluded that community rural tourism has little help from public entities based on social and economic impacts, it was also observed that many of the enterprises that develop community rural tourism are unaware of the existence of a current community tourism network. As recommendations, it can be determined that there is a collaboration between public and private entities for the development of rural community tourism, also that there is a current accountability on the general analysis of the tourist profile every five years and that there is a report on the socioeconomic impacts generated by rural community tourism